2023
DOI: 10.1186/s13578-023-00978-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced liquidity of p62 droplets mediated by Smurf1 links Nrf2 activation and autophagy

Abstract: Background Macro-autophagy/Autophagy is an evolutionarily well-conserved recycling process to maintain the balance through precise spatiotemporal regulation. However, the regulatory mechanisms of biomolecular condensates by the key adaptor protein p62 via liquid-liquid phase separation (LLPS) remain obscure. Results In this study, we showed that E3 ligase Smurf1 enhanced Nrf2 activation and promoted autophagy by increasing p62 phase separation capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Due to this oligomeric property of SQSTM1/p62, it has been suggested that liquid-liquid phase separation (LLPS) may occur when the concentration of SQSTM1/p62 proteins approaches a threshold 29,30 . This phenomenon can lead to the formation of liquid-like condensates known as SQSTM1/p62 bodies which are crucial for autophagic degradation [31][32][33][34] . In fact, we observed the formation of SQSTM1/p62 bodies in HEK293A and STHdhQ7/Q7 cells after the treatment with the autophagy inducer rapamycin (Supplementary Fig.…”
Section: Different Kinetics Of Mhtt Aggregates With Varying Polyq Len...mentioning
confidence: 99%
“…Due to this oligomeric property of SQSTM1/p62, it has been suggested that liquid-liquid phase separation (LLPS) may occur when the concentration of SQSTM1/p62 proteins approaches a threshold 29,30 . This phenomenon can lead to the formation of liquid-like condensates known as SQSTM1/p62 bodies which are crucial for autophagic degradation [31][32][33][34] . In fact, we observed the formation of SQSTM1/p62 bodies in HEK293A and STHdhQ7/Q7 cells after the treatment with the autophagy inducer rapamycin (Supplementary Fig.…”
Section: Different Kinetics Of Mhtt Aggregates With Varying Polyq Len...mentioning
confidence: 99%